Feasibility of augmented reality technology for communication in the construction industry. (October 2021) - Harikrishnan, Archana; Said Abdallah, Abdullatif; Ayer, Steven K.; El Asmar, Mounir; Tang, Pingbo
Abstract: Problem statement: The current shortage of skilled and experienced management personnel in the construction industry makes it necessary to devise solutions that fully leverage the available expertise. Augmented Reality (AR) is an emerging technology that has the potential to provide contextually relevant communication to field engineers and offer value through real-time communication of spatiotemporal details. Purpose: This paper identifies the communication scenarios in which AR may (or may not) be able to replace in-person meetings to address construction-related communication needs, based on data collected from current practitioners. Furthermore, the feedback from practitioners defines contextual factors that would impact their willingness to adopt AR for communication in the domain of construction engineering and management. Methodology: Semi-structured interviews were conducted with practitioners and thematic analysis was performed on the interview data. This process identified trends in the practitioners' responses to reveal their perceptions on use of AR for communication and also the factors that may impact the success of AR for communication in practice. Findings: Practitioners perceived AR to be of value in the following situations: improving the communication between the design team and construction team; effectively leveraging the expertise of experienced personnel; and to aid in inspections. The factors affecting the adoption of this technology were classified into technological factors (e.g. Cost of equipment) and non-technological factors (e.g. Relationship building). Contribution: Many researchers have explored AR for construction, but the vast majority have explored the topic in controlled settings. Conversely, this study relates to real-life practical settings with direct involvement of industry practitioners. Therefore, the contribution of this work is in defining the factors that must be considered if researchers or practitioners intend to realize the theoretical value suggested for AR in practical settings, while taking into account existing challenges.